2004
DOI: 10.1016/s0002-9440(10)63741-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Ets-1 Mediates Ischemia- and Vascular Endothelial Growth Factor-Dependent Retinal Neovascularization

Abstract: Transcription factor Ets-1 has been reported to regulate angiogenesis in vascular endothelial cells. Here, we investigated a mechanism that may regulate the expression of Ets-1 in vascular endothelial growth factor (VEGF)- and hypoxia-induced retinal neovascularization and that may have potential to inhibit ocular neovascular diseases. VEGF and hypoxia increased Ets-1 expression in cultured bovine retinal endothelial cells. The VEGF-induced mRNA increase of Ets-1 was suppressed by a tyrosine kinase inhibitor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 41 publications
(50 reference statements)
0
55
0
Order By: Relevance
“…In addition, a study by Watanabe et al (47) on retinal endothelial cells showed that VEGF and hypoxia-induced Ets-1 mRNA expression and that this was diminished after MEK/ERK1/2 blockade. That study indicated two very important points: 1) MEK/ERK1/2 induced phosphorylation of Ets-1 and enhanced its DNA-binding activity to certain genes; and 2) phosphorylated Ets-1 could bind to its own promoter and regulate its own presence and activity in cells via this feedback mechanism (47). These increases in Ets-1 mRNA level were considered to be associated with the transformation of brain endothelial cells into the angiogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study by Watanabe et al (47) on retinal endothelial cells showed that VEGF and hypoxia-induced Ets-1 mRNA expression and that this was diminished after MEK/ERK1/2 blockade. That study indicated two very important points: 1) MEK/ERK1/2 induced phosphorylation of Ets-1 and enhanced its DNA-binding activity to certain genes; and 2) phosphorylated Ets-1 could bind to its own promoter and regulate its own presence and activity in cells via this feedback mechanism (47). These increases in Ets-1 mRNA level were considered to be associated with the transformation of brain endothelial cells into the angiogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hepatocyte growth factor/scatter factor induces scattering and morphogenesis of epithelial cells through phosphorylation and activation of Ets-1 as the result of MAPK pathway activation (53,54). In addition, a study by Watanabe et al (47) on retinal endothelial cells showed that VEGF and hypoxia-induced Ets-1 mRNA expression and that this was diminished after MEK/ERK1/2 blockade. That study indicated two very important points: 1) MEK/ERK1/2 induced phosphorylation of Ets-1 and enhanced its DNA-binding activity to certain genes; and 2) phosphorylated Ets-1 could bind to its own promoter and regulate its own presence and activity in cells via this feedback mechanism (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the expression level of ETS1 protein in endothelial cells is increased following the addition of growth factors and cytokines that positively contribute to angiogenesis, such as VEGF (Iwasaka et al, 1996;Watanabe et al, 2004) and TNF-a (Goetze et al, 2001). However, the potential modulation of SP100 protein in response to these factors has not been examined.…”
Section: Sp100 and Ets1 Expression Is Induced In Primary Endothelial mentioning
confidence: 99%
“…VEGF increased the level of ETS1 protein over time, but did not significantly affect SP100 or DAXX expression (Figure 1c). ETS1 protein has been shown to increase in response to hypoxic conditions Watanabe et al, 2004), so the modulation of SP100 protein expression using the hypoxia mimetic CoCl 2 was also tested. While ETS1 protein levels increased in response to CoCl 2 , no significant increase in SP100 or DAXX protein expression was observed (Figure 1d).…”
Section: Sp100 and Ets1 Expression Is Induced In Primary Endothelial mentioning
confidence: 99%
See 1 more Smart Citation